ANALYSIS OF PUBLIC SENTIMENT ON GOOGLE PLAY STORE TIJE APPLICATION USERS USING NAÏVE BAYES CLASSIFIER METHOD - Sari, Laila Atikah; Ramadhita, Nindia Fitri; Hasan, Firman Noor (Jurnal Teknik Informatika (Jutif), 2024)
Advances in information technology have an influence on companies and agencies to innovate. The Tije application is one of the innovations that has been made by PT Tranportasi Jakarta which is used by its users. However, each application has advantages and disadvantages, including the Tije application which has an impact on the disruption of the function of supporting user services as the purpose of making this application. This can certainly trigger a response from users which can be submitted through the review column on the Google Play Store platform. This research was conducted to analyze the sentiment of community reviews of Tije application users on the Google Play Store platform using the Naïve Bayes Classifier method. Tije application review data collection is done by web scrapping techniques on the Google Play Store using Google Colab. Then, the collected data will be processed to eliminate inappropriate elements and get sentiment content on each review, whether the review falls into the category of positive or negative sentiment towards the Tije application. The results of this study conclude that users are dissatisfied and disappointed with the services available on the Tije application. This is evidenced by the number of negative sentiments that are more dominant and in the application of the Naive Bayes algorithm in this study, obtained quite good accuracy results of 85.88%.